Digital Marketing Training to Provide Economic Recovery Opportunities for the Community of Jatiwates Jombang East Java - Primaadi Airlangga; Sujono Sujono; Nur Khafidoh; Anti Qurrota A'yuni; Rina Dewi Febrianti; Shoimaturrodliyah Shoimaturrodliyah (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This study addresses the shift from conventional to Digital Marketing strategies in Jatiwates village, Jombang, East Java, in response to pandemic-induced marketing challenges. The research explores the impact of Digital Marketing training on local agricultural promotion, emphasizing its practical significance and economic sustainability. Method: Employing qualitative methods, this research investigates the efficacy of Digital Marketing training through direct engagement, observations, and interviews. Thematic analysis reveals insights into the transition's outcomes and practical implications. Practical Applications: The study highlights how Digital Marketing adoption benefits rural communities reliant on agriculture, enhancing market reach and cost-effectiveness. The findings underscore its potential for similar sectors and geographies, aiding pandemic resilience and sustainable development. Conclusion: The research shows that Digital Marketing training empowers communities like Jatiwates, enabling adaptation to dynamic conditions and improved economic prospects. Embracing digital strategies becomes pivotal for rural development, contributing to practical insights into Digital Marketing's contextual relevance and fostering resilience.